The Independent and Interactive Roles of Procedural, Distributive, and Interactional Justice in Strategic Alliances - Luo, Yadong (Academy of Management Journal, 2007)
This study extends research on strategic alliances by exploring independent and combined effects of distributive, procedural, and interactional justice in these alliances. An integrated framework links cooperation payoffs with organizational justice as perceived by boundary-spanning alliance executives, through whom justice perceptions become parent actions. Analysis of 127 alliances demonstrates that when goal differences between parties are high, the joint effect on alliance performance of procedural and distributive justice is significantly positive. When interactional justice is high, procedural justice exerts a stronger performance effect. This perspective enriches alliance research, especially regarding procedural formalization, incentive structure, and interparty attachment.